THE MODERN COMMUNICATION MANAGEMENT AND IMAGE MAKING IN THE UNITED NATIONS: THE WAYS TO EVALUATE THE COMMUNICATION EFFECTIVENESS - T. Shchors (Вестник университета, 2016)
The article is dedicated to the problems of effectiveness of United Nations communication, aimed to gain a positive image of the Organization. The author gives the detailed analyses of the specific of United nations communication and public information system, describes the main changes in the result of the United nations reform, the main characteristics of new strategic approach to communication and self-evaluation as a method of evaluation of communication results.